MENINGKATKAN, BERSAMA PARA GURU, KEMAMPUAN BERLITERASI SISWA SDN SARIKARYA, YOGYAKARTA - Katharina Endriati Sukamto; Bambang Kaswanti Purwo (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2018)
The present paper is a report of two activities of community service on developing students literacy at Sarikarya Elementary School in Yogyakarta on 20 October 2017 and 11 May 2018. The activities sprout from the result of the research conducted in the same school in August 2017 to find out to what extent the children from class 1 to class 6 make progress in their writing of a descriptive text. By using the result of our research as the basic material for our community service, we had a discussion with the teachers so that they would be more aware of the literacy competence of their students, and by so doing they could help their students develop their students literacy in writing. This community service also aims to discuss with teachers what kind of activities could be carried out in class to support the development.